PENGEMBANGAN E- MODUL KIMIA MENGGUNAKAN APLIKASI FLIP PDF CORPORATE EDITION PADA MATERI LARUTAN PENYANGGA - Novia Anjani Safitri; Elvinawati; Salastri Rohiat (University of Bengkulu, 2022)
ABSTRACT This research aims to find out the exact responses and students’ respons to the developed chemistry e-module. The research was carried out in September-November 2021 at the University of Bengkulu and Senior High School Number 7 Bengkulu City. The development model used in this study is the 4-D (Four-D) model of Thiagarajan which is limited to the development stage. The sample used in the small-scale trial was 12 students from class XII IPA 5. The research data was obtained from the validation of material experts and media experts as well as student responses. From the results of the study, it was found that the chemical e-module in the media aspect was 94.14% and the material aspect was 85.29%, so that the chemical e-module can be categorized as very valid. The results of the student response test to the chemical e-module on a small-scale trial the percentage was 88.33% with a very good category. The results of this study indicate that the chemical e-module using the Flip PDF Corporate Edition application on the buffer material that has been developed is very feasible to be used in the learning process. Keywords : E-module, Model 4-D (Four-D), Flip PDF Corporate Edition